2013
DOI: 10.1186/1756-6606-6-37
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between αCaMKII and calmodulin in living cells: conformational changes arising from CaM -dependent and -independent relationships

Abstract: BackgroundαCaMKII plays central and essential roles in long-term potentiation (LTP), learning and memory. αCaMKII is activated via binding with Ca2+/CaM in response to elevated Ca2+ concentration. Furthermore, prolonged increase in Ca2+ concentration leads to the auto-phosphorylation of αCaMKII at T286, maintaining the activation of αCaMKII even after Ca2+/CaM dissociation. Importantly, the active form of αCaMKII is thought to exhibit conformational change. In order to elucidate the relationships between the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Thus, at least in a crude way, the position of the catalytic region, as measured by FRET, is related to the activity of the enzyme. Direct comparison of the FRET signal of Camui with its enzymatic activity is consistent with this conclusion [ 14 , 15 , 17 ].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Thus, at least in a crude way, the position of the catalytic region, as measured by FRET, is related to the activity of the enzyme. Direct comparison of the FRET signal of Camui with its enzymatic activity is consistent with this conclusion [ 14 , 15 , 17 ].…”
Section: Introductionsupporting
confidence: 67%
“…Understanding the Camui signal, however, requires a precise mapping of the conformational signal reported by the probe onto biochemically defined activation states. Previous work demonstrated a relationships of the Camui FRET signals to the biochemical states of CaMKII under in vitro conditions [ 14 , 15 , 17 , 31 ]. Based on this data, initial studies on the spines of living cells showed that the Camui signal after LTP induction was very short-lived—less than a minute—such that the major (~80%) component decayed with tau1 of ~5–6 sec [ 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…CaM then binds to the CaM-binding domain of CaMKII leading to its conformational change by dissociation of the auto-inhibitory domain from the catalytic domain. Furthermore, prolonged activation of CaMKII by the interaction of CaM-KII with CaM results in the autophosphorylation of threonine-286 (T286) (Kato et al 2013). Phosphorylation at T286 is thought to stabilize the CaM-bound form of CaMKII and therefore, prevents the inactivation of CaMKII kinase activity even after the dissociation of CaM.…”
Section: Camkii Mechanismsmentioning
confidence: 99%
“…The Camui sensor is composed of CaMKIIα tagged with dVenus and GFP fluorophores on its N and C termini, respectively. Upon CaMKII activation, the distance between the termini increases, leading to a decrease in the Forster resonance energy transfer (FRET) between the fluorophores (see also [ 33 , 34 , 35 , 36 ]) and to an increase in GFP lifetime [ 32 ]. Therefore, change in the fluorescent lifetime of the Camui GFP reveals transition of CaMKII between its closed (inactive) and open (active) states [ 32 ].…”
Section: Introductionmentioning
confidence: 99%